Practice Patterns of Central Venous Catheter Placement and Confirmation in Pediatric Critical Care - Veten, Ahmed; Davis, Joshua; Kavanagh, Robert; Thomas, Neal; Zurca, Adrian (Journal of Pediatric Intensive Care, 2021)
Optimal practices for the placement of central venous catheters (CVCs) in critically ill children are unclear. This study describes the clinical practice of pediatric critical care medicine (PCCM) providers regarding CVC placement, including site selection, confirmation practices and assessment of complications. Two-hundred fourteen PCCM providers responded to an electronic survey, including 170 (79%) attending physicians, 30 (14%) fellow physicians, and 14 (7%) advanced practice providers. PCCM providers most commonly place internal jugular (IJ) and femoral CVCs, with subclavian CVCs and peripherally inserted central catheters (PICCs) placed less commonly (IJ 99%, femoral 95%, subclavian 40%, PICC 19%). The IJ is the most preferred site (128/214 (60%)); decreased infection risk is the most common reason for preferring this site. The subclavian is the least preferred site (150/214 [70%]) due to concern for increased risk of complications (51%) and personal discomfort with the procedure (49%). One-hundred twenty-six (59%) of respondents reported receiving formal ultrasound (US) or echocardiography training. Respondents reported using dynamic US guidance for placement in 90% of IJ, 86% of PICC, 78% of femoral, and 12% of subclavian CVCs. Plain radiography (X-ray) was the most preferred modality for confirming CVC tip position (85%) compared with US (9%) and no imaging (5%). Most providers reported using X-ray to evaluate for pneumothorax following upper extremity CVC placement, with only 5% reporting use of US and none relying on physical exam alone. This study demonstrates wide variability in PCCM providers' CVC placement practices. Potential training gaps exist for placement of subclavian catheters and use of US.
Keywords: pediatric critical care; vascular access; central venous catheter; ultrasound; pneumothorax; education